Escrita epistolar e letras do afeto em José Martí - Sampaio, Amanda Leite de (2013)
This work includes the emotional and intellectual trajectory of José Martí right from the artist’s own emotional sources such as personal letters, dedications, travel diaries and notebooks. In the course of José Martí (1853-1895), the letters of affection are the writings which are considered more personal and, in which he shares in a tone of dialogue, feelings and ideas with men and women of his own circle of friends. Observing the frame of the nineteenth century and the Latin American sociopolitical context, the present study highlights the forms of living together in intellectual circles, the experience of exile and places of social circulation of books, periodicals and dissemination of readings.